PENGEMBANGAN ENSIKLOPEDIA ETNOBOTANI TUMBUHAN OBAT TRADISIONAL BATAK TOBA SEBAGAI SUMBER BELAJAR PADA MATERI KEANEKARAGAMAN HAYATI DI KELAS X SMA NEGERI 1 PAHAE JAE - Windi Arningsi Nainggolan; Syarifah Widya Ulfa; Miza Nina Adlini (Jurnal Bionatural, 2025)
An encyclopedia book is a series of books that collect information or descriptions about various things in the fields of art and knowledge, which are arranged alphabetically or by scientific environment. This study aims to see how feasible the Encyclopedia of Traditional Medicinal Plants of Batak Toba is based on the validity and practicality aspects of the Encyclopedia that was developed. This study uses the Research and Development (RnD) research method with the 4D model (Define, Design, Developmet, Dissiminate). The instruments used in this study were validation sheets for material experts, media experts, questionnaires for biology teacher responses and student responses. The results of this study indicate that the Encyclopedia of Traditional Medicinal Plants of Batak Toba that has been developed obtained a percentage of 88.75% (material expert validation) with very valid criteria, 75% (media validation), with valid criteria, and 97.36% (biology teacher responses) with very practical criteria and 91.25% (student responses) with very practical criteria. Based on the description of the results above, it is stated that the Encyclopedia of Traditional Medicinal Plants of Batak Toba that has been developed is valid and practical to use in the learning process. The encyclopedia that has been developed can be used as a learning resource for both students and teachers on the material of biodiversity.